Morphological variability and taxonomy of Coraebus hastanus Gory & Laporte de Castelnau, 1839 (Coleoptera: Buprestidae: Agrilinae: Coraebini: Coraebina) - Xu, Hongxia; Kubáň, Vítězslav; Volkovitsh, Mark G.; Ge, Siqin; Bai, Ming; Yang, Xingke (Zootaxa, 2013)
Coraebus hastanus Gory & Laporte de Castelnau, 1839 is easily distinguished from the other species of the genus Corae-bus Gory & Laporte de Castelnau, 1839. It was divided into three subspecies, but the main diagnostic characters were vari-able. In order to understand the morphological variability and taxonomy of subspecies of C. hastanus, shape of elytral apex, lateral margin of elytra and the aedeagi were analyzed using geometric morphometric and traditional morphometric approaches. Based on the results and distribution patterns of the three subspecies, C. hastanus oberthueri Lewis, 1896 is treated as synonym of C. hastanus Gory & Laporte de Castelnau, 1839, and C. hastanus ephippiatus Théry, 1938 is ele-vated to species rank, and these two species are also redescribed and illustrated.